The theory of harm under the Malaysian competition Act 2010 - Abdul Rahman, Nasarudin; Haniff, Ahamat; Zuhairah Ariff, Abdul Ghadas (Universiti Putra Malaysia Press, 2017)
The Malaysian Competition Act 2010 (CA 2010) seeks to promote the process of competition in the market by preventing anti-competitive conduct that harms competition. However, ‘harm to competition’ is not clearly defined in the Act and neither are its subsequent guidelines. Without proper application of the theory of harm, the competition authority will not be able to provide a consistent approach to the assessment of the competition issues especially in determining whether or not a conduct is anti-competitive. This paper aims to analyse how and to what extent the Malaysian Competition Commission (MyCC) applies the theory of harm in competition law analysis. This paper argues that there is no standard definition of what ‘harm to competition’ means in the context of Malaysian competition law. ‘Harm to competition’ may be interpreted as harm to the competitive process and consumers (final consumers). It may also be narrowly interpreted as harm to market mechanism or the ability to compete, through, for example, unjustified exclusion of rivals from the market without the need to prove that conduct was harmful i.e. reduced aggregate consumer welfare. In most situations, the issue of competitive harm is not about interpretation but rather of proof that a particular conduct really harmed competition and consumers